Analysis of operability parameter changes in neoadjuvant treatment with chemotherapy and anti-PD-1/PD-L1 - M Sereno; A Collazo-Lorduy; Y Garitaonaindia; D Gómez de Antonio; J Baena Espinar; C Aguado de la Rosa; P Cruz Castellanos; S Falagán Martínez; LE Chara Valverde; R López-Castro; A López-Martin; J Rubio-Pérez; et al. (Cancer Treatment and Research Communications)
Background: The adoption of combined chemotherapy (CT) and immunotherapy (IO) has advanced neoadjuvant therapy (NA) for non-small cell lung cancer (NSCLC), but data on functional impacts are limited. This multicenter retrospective study evaluates respiratory function in NSCLC patients undergoing NA. Methods: From 2020 to 2024, 186 patients treated with CT or CT-IO (anti-PD-1/PD-L1) were analyzed. Respiratory tests (DLCO, FEV1, FVC) pre- and post-NA were compared, alongside clinical, pathological, and surgical variables. Results: Median age: 68; 66.6 % male; 93 % smokers/ex-smokers, histologies: Squamous and adenocarcinoma (46 % each), DLCO decline was greater in CT-IO vs. CT (-12.6 % vs. -7.8 %, p = 0.007) and CT-IO showed increased FEV1 (+3.8 % vs. -2.5 %, p = 0.001) and FVC (+3.7 % vs. -0.7 %, p = 0.003), surgery rate: 85.7 % (lobectomy most common at 83.3 %) and no differences in complications were found except for 9 immune-mediated events in CT-IO. Conclusions: CT-IO impacts DLCO more but improves FEV1 and FVC compared to CT. These findings warrant further validation in prospective studies.